2017
DOI: 10.7717/peerj.2885
|View full text |Cite
|
Sign up to set email alerts
|

A critical issue in model-based inference for studying trait-based community assembly and a solution

Abstract: Statistical testing of trait-environment association from data is a challenge as there is no common unit of observation: the trait is observed on species, the environment on sites and the mediating abundance on species-site combinations. A number of correlation-based methods, such as the community weighted trait means method (CWM), the fourth-corner correlation method and the multivariate method RLQ, have been proposed to estimate such trait-environment associations. In these methods, valid statistical testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 36 publications
3
51
0
Order By: Relevance
“…ter Braak et al. () detected moderate type I error rate inflation in the max test using GLM for testing the trait–environment association. In this study, we showed similar problems using the fourth‐corner and CWM‐ and SNC‐based methods in both the log‐linear model and the two‐dimensional Gaussian model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ter Braak et al. () detected moderate type I error rate inflation in the max test using GLM for testing the trait–environment association. In this study, we showed similar problems using the fourth‐corner and CWM‐ and SNC‐based methods in both the log‐linear model and the two‐dimensional Gaussian model.…”
Section: Discussionmentioning
confidence: 99%
“…ter Braak et al. () argued that trait–environment interaction is scale‐ and thus model‐dependent. Arguably, there is a trait–environment interaction in this scenario when viewed on any other scale than the log‐linear scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our approach is an extension of the community assembly via trait selection (CATS) (Warton et al 2015) following a multivariate regression specification (Jamil et al 2013, ter Braak et al 2017) and a joint species distribution model specification (Pollock et al 2014, Ovaskainen et al 2016. Our approach is an extension of the community assembly via trait selection (CATS) (Warton et al 2015) following a multivariate regression specification (Jamil et al 2013, ter Braak et al 2017) and a joint species distribution model specification (Pollock et al 2014, Ovaskainen et al 2016.…”
Section: Statistical Analysesmentioning
confidence: 99%